The Use of Team Teaching Methods to Increase Student Interest and Achievement - Maija, Groop; Tiinamaija, Groop; Antti, Thorn (World Psychology, 2023)
It is undeniable that students will definitely experience a decline in the learning process. In the learning process students who have a lack of motivation tend to fail to increase the passion for learning. So that it will cause students to find it difficult to achieve targets in improving achievement at school. The researcher's goal in the research to be carried out is to determine the right method in increasing student interest and achievement by using a team teaching method that involves students and educators in the research process. Thus, in this study researchers used qualitative methods conducted by direct interviews and could facilitate researchers in collecting data and asking in detail. From the research conducted, it was found that by using the team teaching method, students will be more controlled in participating in active learning in the classroom. The obstacles that researchers found during the research were that the schools concerned had difficulties when applying the team teaching method in the classroom due to the limited knowledge of teachers to determine the right way of team teaching. From the research conducted, researchers can conclude that students who do not receive direct motivation will affect the enthusiasm and learning outcomes of students, to prevent this, researchers try to use the team teaching method in the learning process and find the results that team teaching can help students play an active role while in class